Challenges of Integrating Generic Employability Skills into Bachelors Degree Level at Libyan Universities: تحديات دمج مهارات التوظيف العامة في برامج البكالوريوس بالجامعات الليبية - Aflifel, Nabil Yosef; Brydan, Rashad (Journal of North African Economies, 2025)
This study aims to identify the challenges faced Libyan higher education institutions while defying and integrating the required generic employability skills (GES). The reason for choosing this topic because it is now at the centre of attention for Libyan Universities and higher education institutions. The study followed a qualitative and quantitative research methodology in order to ensure the quality of the targeted GES. As well as, questionnaires, and personal interviews were used for date collection and a specific research sample of 100 Libyan University academics who participated to decide the 10 most important GES and visual analysis model was adapted to analyse the collected data accordingly. The authors after discovering the required GES have concluded that organisational, financial, academic and cultural challenges are delaying integrating employability skills into Libyan University Programs, furthermore it’s recommended that a state strategic plan should take place to overcome these challenges, additionally further studies are still needed about this topic to find the best way forward for the Libyan higher education sector.